2023
DOI: 10.1055/s-0042-1751505
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Carbohydrate Conjugates: Pyrano[3,2-c]quinolones

Brajendra K. Singh,
Sumit Kumar,
Aditi Arora
et al.

Abstract: A facile and efficient protocol for the diastereoselective synthesis of pyrano[3,2-c]quinolone carbohydrate derivatives from Perlin aldehydes and 4-hydroxyquinolones has been developed using a one-pot condensation at room temperature. In this investigation, glucose and galactose were employed as inexpensive starting materials to synthesize two sets of pyrano[3,2-c]quinolone-based carbohydrate conjugates. A total of sixteen novel compounds were successfully synthesized using this methodology in good to excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In addition to our on-going work on the synthesis of novel heterocyclic molecules and unique synthetic techniques utilizing a variety of intermediates such as methyl dithiocarboxylates, xanthate esters, and 2-oxo-2-(amino) ethanedithioates, 16–25 herein, we developed an operationally simple and novel method for the synthesis of mono-, di- and tri-substituted thiazoles using alkyl 2-amino-2-thioxoacetates intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to our on-going work on the synthesis of novel heterocyclic molecules and unique synthetic techniques utilizing a variety of intermediates such as methyl dithiocarboxylates, xanthate esters, and 2-oxo-2-(amino) ethanedithioates, 16–25 herein, we developed an operationally simple and novel method for the synthesis of mono-, di- and tri-substituted thiazoles using alkyl 2-amino-2-thioxoacetates intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…24–32 Retrosynthetic analysis suggested that the 1,3-oxazolidine moiety could be constructed using amine, epoxide, and methylene units as precursor building blocks (Scheme 1). The ring opening of epoxides is widely recognized for creating a potential electrophilic site in Friedel–Crafts reactions, 33 serving as an essential step in the synthesis of 1,3-oxazolidine.…”
Section: Introductionmentioning
confidence: 99%